Analisis Anggaran Sebagai Alat Pengawasan Pajak Reklame Pada Dinas Pendapatan Daerah Kota Medan - Kusmilawaty, K (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2018)
Taxes are the dues to the State (imposed) owed by the taxpayer with the provisions of the applicable legislation, with no accomplishment gets back and the point is to finance public expenditure-expenditure relating to the task of the State to the Government. Advertisement tax scrutiny already good or not, can be seen from the realization of tax revenue with advertising budgets or targets set earlier. Where the report based on data known to the realization of tax revenue on the Revenue Department of the city of Medan from the year 2013 to 2017 years occurred a considerable difference between the budget and its realization which demonstrates that the achievement of performance acceptance advertisement tax are still not adequate. In this study, researchers conducted a study using a descriptive approach. Descriptive research is research that aims to find out the application variables examined so that the conclusion that apply generally. Advertisement tax revenue on the Revenue Service Area Medan city as a whole is still less well, can be seen from Budget tax revenue advertising is always set at the beginning of the period by the head of the Agency upon consideration of the various parties, particularly from the planning section, the section of the budget and sexy analysis and Control.